Rola funduszy strukturalnych w rozwoju grup producentów rolnych - Kotala, Andrzej; Brzozowska, Anna (The Role of Structural Funds in the Development of Agricultural Producers' Groups, 2005)
The important element to adjust Poland to the European Union structures is the creation of agricultural producers' groups. The tasks done jointly by farmers contribute to the realisation of objectives and rules of the Common Agricultural Policy. According to aforementioned policy plenty of undertakings supporting agricultural producers' groups are financed by structural funds. The access to the European Union funds as well as the possibility of competition with economically strong Union farms will depend on the level of development of producers' organizations in Poland. To encourage farmers to practical activities towards adjusting the new requirements, an economical incentives to producers' cooperation are presented. However, the producers must have been up to difficult conditions imposed by the European Union in the area of supporting the agricultural producers' groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 478-483